Comparison of 3 Different Systems for Non-wire Localization of Lesions in Breast Cancer Surgery - Gabrielova, Lucie; Selingerova, Iveta; Zatecky, Jan; Zapletal, Ondrej; Burkon, Petr; Holanek, Milos; Coufal, Oldrich (Clinical breast cancer, 2023)
PURPOSE: Localizing breast lesions by marking tumors and their detection using probes during surgery is a common part of clinical practice. Various nonwire localization systems were intended to be compared from different perspectives. METHODS: Various measurement experiments were performed. Localization techniques, including radioactive seed (RSLS), magnetically guided (MGLS), or radar (SLS), were compared in signal propagation in water and tissue environments, signal interference by surgical instruments, and the practical experience of surgeons. Individual experiments were thoroughly prospectively planned. RESULTS: The RSLS signal was detectable at the largest evaluated distance, ie, 60 mm. The SLS and MGLS signal detection was shorter, up to 25 mm to 45 mm and 30 mm, respectively. The signal intensity and the maximum detection distance in water differed slightly depending on the localization marker orientation to the probe, especially for SLS and MGLS. Signal propagation in the tissue was noted to a depth of 60 mm for RSLS, 50 mm for SLS, and 20 mm for MGLS. Except for the expected signal interferences by approaching surgical instruments from any direction for MGLS, the signal interruption for RSLS and SLS was observed only by inserting instruments directly between the localization marker and probe. Moreover, the SLS signal interference by instrument touch was noted. Based on surgeons' results, individual systems did not differ significantly for most measurement condition settings. CONCLUSION: Apparent differences noted among localization systems can help experts choose an appropriate system for a specific situation or reveal small nuances that have not yet been observed in clinical practice.
Keywords: mikrochirurgie; zaměřovací značky pro radioterapii; Humans; Female; Radioactive seed localization; Breast; lidé; Radar localization; Microsurgery; Breast Neoplasms; ženské pohlaví; Magnetically guided localization; voda; segmentální mastektomie; nádory prsu; Water; Mastectomy, Segmental; Lesion localization; Fiducial Markers; prsy